2014
DOI: 10.4028/www.scientific.net/amr.1010-1012.1531
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation on the Influence of Flammable Gas Concentration on Explosion Peak Pressure

Abstract: This paper simulates the alternation of the maximum explosion overpressure on the different condition of the concentration based on the fluent software. The results show the maximum explosion overpressure increases in the earlier stage and then decreases in the later stage because of the different flammable gas concentration: the maximum explosion overpressure enhanced in 6% gas concentration and drops in 12% gas concentration; it augments in 6% gas concentration and drops in 12% gas concentration with the joi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Explosion mechanisms have been explored to estimate the influence of gas concentration on gas explosions. Ma 24 simulated the alternation of the maximum explosion overpressure under different concentration conditions based on Fluent software. The results showed that the maximum explosion overpressure increases in the earlier stage and decreases in the later stage in gas explosion concentration limits.…”
Section: Introductionmentioning
confidence: 99%
“…Explosion mechanisms have been explored to estimate the influence of gas concentration on gas explosions. Ma 24 simulated the alternation of the maximum explosion overpressure under different concentration conditions based on Fluent software. The results showed that the maximum explosion overpressure increases in the earlier stage and decreases in the later stage in gas explosion concentration limits.…”
Section: Introductionmentioning
confidence: 99%